Practicality of Student Worksheets (LKS) on Sound Waves Based on a Generative Learning Model Using Cognitive Conflict Strategies to Facilitate Creative Thinking Skills in 11th Grade High School Students (Pillar of Physics Education : Jurnal Berkala Ilmiah Pendidikan Fisika, 2026)
Students' creative thinking skills are in the moderate category with percentages in the indicators of fluency(46%), flexibility (55%), originality (58%), and elaboration (43%). Worksheets are the main teaching material inthe learning process. The worksheets used are not yet optimal in facilitating creative thinking skills because thelearning model applied does not encourage the exploration of creative ideas. The purpose of this study is toproduce valid and practical sound wave worksheets based on a generative model to facilitate the creative thinkingskills of grade XI students. This research method is Research and Development with a 4-D model (define, design,develop, and disseminate). The research subjects were five physics experts from FMIPA UNP as validators, threephysics practitioners, and 23 users from class XI SMAN Padang. The research instruments were validation andpracticality sheets analyzed using Aiken's V index and percentage techniques. The experts assessed the validity ofthe worksheets in terms of the substance of the learning content (0.83), visual communication display (0.93),worksheet content (0.91), generative learning model syntax (0.87), and creative thinking indicators (0.88).Practitioners and users have assessed the LKS as very practical, with scores of 88% and 93%. It was concludedthat the generative model-based sound wave LKS developed is highly valid and practical. Practitioners shoulduse the LKS, and users should use it to facilitate the creative thinking skills of 11th grade students.